Compreensão das implicações de valor e de fluxo no contexto de financiamento coletivo a partir dos projetos “Tem alguém que nos odeia” e “Toureando o diabo” - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The paper’s investigation discusses the value and fluxes’ implication in the exchange features of crowdfunding’s context in the play "Tem alguém que nos odeia" and in the book "Toureando o diabo" in site Catarse .Here we review concepts of economy of culture, cultural Market of goods and services and value typologies; describe the crowdfunding’s process from Catarse’s dynamics and; relate the theoretical research to practical issues through the examples of cultural projects: theatrical and other literary. This, through bibliographical and documentary research and the study of these cases. Into a more global understanding of the issues, we combine to raise funds by crowdfunding "parallel ideas market to things market” a quote from Throsby (2001). This is because even though you have an idea to publish the project, you also have to understand the artworks within their production process. For the setting of the minimum funding amount covers the cost of a project to be administered and executed with excellence.
Keywords: Cultura; Financiamento de projetos; Economia; Culture; Project funding; Crowdfunding; CNPQ::CIENCIAS SOCIAIS APLICADAS